Analisis Google Terjemahan Yang Menggandung Ungkapan Bahasa Seksisme Terjemahan Bahasa Inggris - Muji Endah Palupi (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The phenomenon of sexist language is closely related to the concept of gender that has been structured at the level of language correctionalism. Therefore, this sexist word or phrase is actually made by people who are influenced by views on both types of gender. Often in  language sexism  more gender-oriented or degrading. One language that is considered to contain a lot of vocabulary and expression of Sexist is  English Language. This is because English Language is an International Language. English Language that is rich in vocabulary and many elements of language are absorbed. This research will be explain   types  of  sexist language found in the results of the English Translation. Analysis of the accuracy of translations in English  language will be studied in the science of learning foreign languages. That actually English Language is a language that is more inclined to sexism than other languages. This is evident in most translations which are considered  inaccurate and ambiguous which contain sexist elements in the results of the translation into other languages. Keywords: Google Translation, Sexism Language, English Translation